The Influence of Spiritual Therapy Emotional Freedom Technique (SEFT) Against Self-Concept of Breast Cancer Patients with Mastectomy - Esi Afriyanti; Bunga Permata Wenni (Jurnal Keperawatan Padjadjaran, 2018)
Mastectomy is a surgical treatment of breast cancer can result in permanent changes in the appearance of women. this change can cause a negative change in a woman's self-concept. If the self-concept impairment continues it will lead to emotional weakness. Individuals will be depressed and feel constantly anxious, emotional frustrations are getting worse, making the individual create self-destruction. For that needed therapy that can overcome the negative problems of this self-concept of Spiritual Therapy Emotional Freedom Technique (SEFT).The purpose of this study was to identify the effects of SEFT therapy on self-concept in breast cancer women with mastectomy. This study uses quasi experimental design with one group pretest-posttest design approach with inclusion criteria willing to be the subject of research, conscious, no hearing loss or self-concept cognitive impairment, has never done SEFT therapy, interacted with family and community at least 1 week post mastectomy . This therapy is done for 3 days on 33 subjects. Data were analyzed by chi square statistic test with 95% CI with significance p <0,05.The result of this research is prior to being given SEFT treatment from 33 respondents, 4 respondents (12,1%) have positive self concept, and the majority of 29 respondents (87,9%) have negative self concept. However, after SEFT treatment there was an increase in self-concept of respondents with positive self concept as many as 10 people (30.3%) and still have negative self concept as many as 23 people (69,7%). Once tested with chi-square statistical test, there are differences in self-concept before and after SEFT. It is advisable to practice nursing to use this therapy as a therapy to prevent self-conceptual disorder in breast cancer patients who have mastectomy